Pengaruh Kepercayaan dan Pemahaman Terhadap Minat Berzakat di Lembaga Amil Zakat Masjid Baitul Ihsan - Salmi Afrida; Tiara tiara; Eka Putra (Journal Islamic Economic and Bussines Studies, 2022)
One of the problems faced by the Indonesian state today is economic problems, as a country whose population is predominantly Muslim, Islamic demands and tips are very important to be realized, one of which is zakat. is a lack of public trust and understanding. This study aims to determine the effect of trust and understanding on interest in paying zakat at the Baitul Ihsan Mosque Amil Zakat Institution. The method used in this research is quantitative with multiple linear regression data analysis. The results of this study indicate that trust has an effect on interest in paying zakat in terms of the tcount 2.884 > ttable 1.993. understanding affects the interest in paying zakat can be seen from tcount 3,607 > ttable 1,993. Trust and understanding together affect the interest in paying zakat as seen from theF valuecalculated 37.682 > Ftable 3.12.